Supply chain analysis of smokeless charcoal from maize residues - Korrakot Yaibuathet Tippayawong; Suphanat Panyakom; Chayakorn Suriyanarakorn; Kengkamon Wiratkasem; Nakorn Tippayawong (Energy Reports, 2020)
Open burning of agricultural residues after harvesting season is usually practiced as a disposal means for highland farms. The practice has partially contributed to the haze problem in the northern region of Southeast Asia during February to April every year. This can drastically affect human health in the long run. In this work, alternative means to utilize maize residues as a bio-renewable fuel source is explored. These maize residues can potentially be used as a raw material to substitute or partially replace wood chips in production of smokeless charcoal. Local charcoal producers in Maehongson, northern Thailand have recently looked into alternative raw materials for smokeless charcoal production since the demand for domestic and aboard has shoot up to about 6000 tons this year. Possibility of using maize residues is paramount. According to such requirement, this work focused on cost analysis of transforming maize residues into high-added-value smokeless charcoal. The analysis covered from maize harvesting and residue collection methods, logistics approach to charcoal production site, production cost and product transportation cost. Primary and secondary data collection, site survey, interviews with stakeholders and cost modeling were performed. It was found that the maize farmers could earn up to 15 USD/ton from sales of the maize residues to charcoal production plants, while the plants remain profitable.
Keywords: 330; Agricultural residues; Cost analysis; Environmental policy; Smokeless charcoal; Sustainable waste management